PENGARUH EARNING PER SHARE (EPS), DIVIDEND PER SHARE (DPS) DAN FINANCIAL LEVERAGE (FL)TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Ariswandi Sang Putra (Universitas Negeri Padang, 2018)
The ups and downs of stock prices depend on the attractive tug strength between demand and supply of stocks in the capital market. Understanding of stock prices and the factors that affect the changes is very important because it can provide information for investors or prospective investors in investing in the form of shares. For investors information on Earning Per Share, Dividend Per Share and Financial Leverage become a very basic requirement in decision making needs. Therefore, the researcher is interested in doing research about the effect of: 1) earning per shere on stock price, 2) dividend per share to stock price, 3) financial leverage to share price of a company. The population of this study are all manufacturing companies listed on the Indonesia Stock Exchange period 2011-2015. The method of selecting the sample using purposive sampling, samples obtained 53 companies period 2011-2015, so that 265data obtained in this study. The variables in this study consisted of EPS, DPS and FL as independent variable and stock price as dependent variable. Methods of data collection using documentation to obtain data on EPS, DPS, FL and stock prices. Data analysis used multiple regression analysis. The results of this study indicate that earnings per shere have a significant positive effect on stock prices, dividend per share positively insignificant to stock prices, and financial leverage positively insignificant effect on stock prices.Keyword: EPS ,DPS,FL, Stock Price